Six Potential Superior Durian Plants Resulted by Cross Breeding of D. zibethinus and D. Kutejensis From East Kalimantan, Indonesia: Initial Identification - Kurniadinata, Odit Ferry; Wenpei, Song; Zaini, Achmad; Rusdiansyah, Rusdiansyah (Yayasan Pertanian Tropika Indonesia (YPTI), 2019)
Kalimantan Island is rich in genetic resources and species diversity of Durio spp. Of the 27 durian species in the world, 18 species are found in Borneo. The large number of Durio species that grow in Kalimantan illustrates that this area is the most important distribution center for durian relatives. Two of the best-known edible durians in East Kalimantan are Durian (Duriozibethinus) and Lai (Durio kutejensis). However, as a plant with a cross-pollination mechanism, there are many results of natural crosses between the two. The study aimed to identify Durian x Lai plants in Loa Kulu, Kutai Kertanegara, East Kalimantan Province, Indonesia as the superior local fruit crops potentially agribusiness industry. This research was carried out by collecting data and information about the morphological characteristics of the plants and fruits from D. Zibenthinus x D. Kutejensis. The results of the study successfully identified 6 potentially superior plants that are believed to be the result of a cross between D. Zibenthinus x D. kutenjensis. The 6 potential superior plants were found to have different morphological characters. This is the initial identification and being a basis of the next research phase, which is to identify the morphology of trees, flowers, and fruit to obtain new cultivars crossing D.zibenthinus and D. Kutejensis which have superior potential as superior commodities from East Kalimantan.